Analisis kedekatan emosional dalam interaksi sosial antara penjual kantin dan mahasiswa di kampus 1 UIN Malang: Dinamika relasi sosial di lingkungan kampus - Fitri, Layyinah Salsabila (Maliki Interdisciplinary Journal, 2026)
This article seeks to explore the emotional closeness established through social interactions between canteen vendors and students at Campus 1 of UIN Malang. The interactions extend beyond transactional activities and develop into ongoing, personal social relationships. A qualitative research design was applied, utilizing observation and in-depth interviews with both canteen vendors and students as data collection methods. The results reveal that emotional closeness is fostered through frequent communication, openness, mutual familiarity, and the emergence of trust and comfort. Within these interactions, canteen vendors often act as attentive listeners and provide emotional care and support for students. Such relationships contribute positively to stronger student attachment to canteen vendors, the creation of a comfortable canteen atmosphere, and the reinforcement of social connections within the campus environment. Consequently, social interactions in campus canteens play a significant role in promoting emotional bonds and social harmony among members of the academic community.